METAFORA DAN NILAI BUDAYA DALAM PERIBAHASA BAHASA MELAYU KUTAI - Wenni Rusbiyantoro (Kantor Bahasa Kalimantan Timur, 2016)
The proverb of Melayu Kutai language is the manifestation of the nature and natural characteristics in Kutai people's homes in Kutai Regency. The proverb is used as a form of satire that contains advices for its speakers. This research is a qualitative descriptive study that examines metaphors and cultural values in Kutai Melayu proverb. In the proverb, there are metaphors referring to animals and cultural values representing the working mentality, attitudes, perceptions, behaviors, ethics, and morals. It shows about the use of language metaphorically as an expression that contains the values of culture that has long existed in Kutai community.